Halogenated dicyanobenzene-based photosensitizer (3DPAFIPN) as a thermally activated delayed fluorescence (TADF) used in gram-scale photosynthesis 3,4-dihydropyrimidin-2-(1H)-one/thione derivatives via a consecutive visible-light-induced electron-transfer pathway - Mohamadpour, Farzaneh; Amani, Ali Mohammad (Frontiers in Chemistry, 2024)
Background: Organic dyes often have shorter lifetimes in the excited state, which is a major obstacle to the development of effective photoredox methods. The scientific community has shown a great deal of interest in a certain class of organic chromophores because of their unique characteristics and effectiveness. One characteristic of the molecules under research is thermally activated delayed fluorescence (TADF), which is only observed in molecules with a tiny energy gap (often less than 0.2 eV) between their lowest two excited states, i.e., singlet excited state (S1) and triplet excited state (T1). The extended singlet excited states arising from TADF and the simplicity with which their redox potentials may be altered make the isophthalonitrile family of chromophores an attractive option for organic photocatalyst applications. Methods: The Biginelli reaction between β-ketoesters, arylaldehydes, and urea/thiourea has been used to build a sustainable technique for the production of 3,4-dihydropyrimidin-2-(1H)-one/thione derivatives. In the present study, the development of a green radical synthesis approach for this class of compounds is addressed in depth. As a photocatalyst, a new halogenated dicyanobenzene-based photosensitizer was employed in this study. As a renewable energy source activated by a blue LED, it was dissolved in ethanol, at room temperature in air atmosphere. The primary objective of this research is to employ a novel donor-acceptor (D-A) based on halogenated cyanoarene that is affordable, easily available, and innovative. Findings: The 3DPAFIPN [2,4,6-tris(diphenylamino)-5-fluoroisophthalonitrile] photocatalyst, a thermally activated delayed fluorescence (TADF), induces single-electron transfer (SET) in response to visible light, offering a straightforward, eco-friendly, and highly efficient process. Additionally, we determined the 3,4-dihydropyrimidin-2-(1H)-one/thione derivatives turnover frequency (TOF) and turnover number (TON). It has also been demonstrated that gram-scale cyclization is a workable method for industrial purposes.